HUBUNGAN PENGETAHUAN & SIKAP DENGAN KEPATUHAN IBU HAMIL MENGONSUMSI TABLET TAMBAH DARAH DI TIYUH PANARAGAN LAMPUNG - Muliani, Usdeka; Bertalina, Bertalina (HEALTHY : Jurnal Inovasi Riset Ilmu Kesehatan, 2025)
The purpose of this study was to determine the relationship between knowledge and attitudes with the compliance of pregnant women in consuming iron tablets. This type of research is a descriptive method with a cross-sectional approach. The data collection location was in Tiyuh Panaragan, Tulang Bawang Tengah District, West Tulang Bawang Regency. The sample was the population of pregnant women in the Tiyuh Panaragan area who underwent examinations and were recorded by the village midwife and received iron tablets, namely 35 pregnant women. Measurement of knowledge and attitudes used a knowledge and attitude questionnaire, and measurement of compliance with iron tablet consumption used the MMAS-8 (Morisky Medication Adherence Scale) questionnaire. From the results of the study, it was obtained that most of the respondents were around 20-35 years old, namely 71.4%, the highest level of education was junior high school, namely 37.1%, and the highest occupation was unemployed, 77.1%. More than half of the respondents had anemia (54.3%), while the level of knowledge and attitudes of the respondents were mostly in the good category, namely good knowledge 74.3%, and good attitude (positive) 85.7%, while the level of compliance of respondents in consuming TTD was mostly in the less category, namely 54.3%. The results of the bivariate analysis showed that there was a significant relationship between respondent knowledge and the level of compliance of respondents in consuming TTD with a value of p = 0.005 and there was no significant relationship between respondent attitudes and the level of compliance of respondents in consuming TTD with a value of p = 0.347. From the results of the study, it is recommended that pregnant women's awareness be increased to consume good TTD in order to achieve optimal nutritional status for the mother and her fetus. ABSTRAKTujuan penelitian untuk mengetahui hubungan pengetahuan, dan sikap dengan kepatuhan ibu hamil dalam mengonsumsi tablet tambah darah. Jenis penelitian ini adalah metode deskriptif dengan pendekatan cross sectional. Tempat pengambilan data di Tiyuh Panaragan Kecamatan Tulang Bawang Tengah, Kabupaten Tulang Bawang Barat. Sampel adalah populasi ibu hamil yang berada di wilayah Tiyuh Panaragan  yang melakukan pemeriksaan dan tercatat oleh bidan desa dan mendapat tablet tambah darah yaitu sebanyak 35 ibu hamil. Pengukuran pengetahuan dan sikap menggunakan kuesioner pengetahuan dan sikap, serta pengukuran kepatuhan konsumsi tablet besi menggunakan kuesioner MMAS-8 (Morisky Medication Adherence Scale). Dari hasil penelitian diperoleh sebagian besar usia responden sekitar 20-35 tahun yaitu 71,4%, tingkat pendidikan terbanyak SMP yaitu 37,1%, dan pekerjaan terbanyak tidak bekerja 77,1%. Lebih dari setengah responden mengalami anemia (54,3%), adapun tingkat pengetahuan, dan sikap responden  terbanyak dalam katagori baik yaitu pengetahuan baik 74,3%, dan sikap baik (positip) 85,7%, adapun  tingkat kepatuhan responden  dalam mengkonsumsi TTD terbanyak dalam katagori kurang yaitu 54,3%. Hasil analisis bivariate diketahui ada hubungan yang signifikan antara pengetahuan responden dengan tingkat kepatuhan responden  dalam mengkonsumsi TTD nilai p= 0,005 dan tidak ada hubungan yang signifikan antara sikap responden dengan tingkat kepatuhan responden  dalam mengkonsumsi TTD nilai p= 0,347. Dari hasil penelitian disarankan agar lebih ditingkatkan kesadaran ibu hamil untuk mengkonsumsi TTD yang baik agar dicapai status gizi yang optimal bagi ibu dan janinnya.